Validating a low-cost, consumer force-measuring platform as an accessible alternative for measuring postural sway - Bartlett, K. A.; Forth, K. E.; Layne, C. S.; Madansingh, S. (Journal of Biomechanics, 2019)
The Zibrio SmartScale is a low-cost, portable force platform designed to perform an objective assessment of postural stability. The purpose of the present study was to validate the center of pressure (COP) measurements in the Zibrio SmartScale. Simultaneous COP data was collected by a Zibrio SmartScale and a laboratory-grade force platform (LFP) under the dynamic motion of an inverted pendulum device intended to mimic the sway of a standing human. The inverted pendulum was placed on the Zibrio SmartScale which was placed on the LFP. The pendulum was then displaced to angles of 3° and 5° in both the anterior-posterior (AP) and medial-lateral (ML) directions. The findings of this study show low mean average error (MAE) among the measures taken simultaneously upon the LFP and Zibrio SmartScale with no appreciable difference in error in either AP or ML COP directions. Averaged over repeated trials, the MAE did not surpass 0.5 mm. This represented 0.4% of the total range (±50 to 60 mm in 5° displacement trials) of simulated COP. The results of this study strongly indicate that the Zibrio SmartScale can perform adequately as a light-weight and low-cost alternative method of COP measurement in comparison to a traditional LFP.